Design and implementation of a smart sterilizing device to solve the doorknob contamination problem - Satam, Ihab Abdulrahman; Zaenal, Mohammed U. (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction: In 2020, the World Health Organization announced that Corona virus (Covid-19) is a global pandemic. Since then, social distancing and sterilization have become essential as precaution measures to decrease the infection. The risk of Covid virus spread led people, industries as well as governments to implement several approaches to control the transmission rate of the virus. During their daily life activities such as work, shopping, eating, etc. people touch a lot of surfaces and also open a large number of doors. This is considered to be one of the fastest ways to spread viruses because many people touch door handles which are generally rarely cleaned.Method:  In this paper, the implementation of a cost-effective smart device has been presented.  The device sprays ethanol onto a doorknob from an ethanol sterilizer after any person touches the knob. The sensor detects a hand touching the knob, after that a signal is sent to the Arduino for processing, and then after a 4.5-sec delay, the Arduino sends a signal to the water pump to pump ethanol alcohols through the nozzle directly to the knob.Results: The device shows precise and accurate results regarding the number of uses and the temperature of the surrounding ambient.Conclusion: The system is applicable in offices and public buildings. Due to its functionality, it can be of great assistance in decreasing the contamination of doorknobs.
Keywords: smart sterilizer; arduino; actuators; doorknob; water pump